Barriers to help-seeking, accessing and providing mental health support for medical students: a mixed methods study using the candidacy framework - Elena Sheldon; Naseeb Ezaydi; Lauren Desoysa; Jasmine Young; Melanie Simmonds-Buckley; Prof Daniel Hind; Prof Chris Burton (BMC, 2024)
Abstract Background The mental health of medical students is a national and international problem increasing in both demand and acuity. Medical students face barriers to accessing mental health support that is clinically effective, timely and appropriate for their needs. This mixed methods study aimed to explore experiences of these barriers and the challenges to health service delivery aligned to the Candidacy Framework. Methods One hundred three medical students studying at The University of Sheffield completed an online survey comprising the CCAPS-34 and follow-up questions about service access and use. Semi-structured interviews with a nested sample of 20 medical students and 10 healthcare professionals explored barriers to service access and provision. A stakeholder panel of medical students and professionals met quarterly to co-produce research materials, interpret research data and identify touchpoints by pinpointing specific areas and moments of interaction between a medical student as a service user and a mental health service. Results Medical students who experienced barriers to help-seeking and accessing support scored significantly higher for psychological symptoms on the CCAPS-34. Uncertainty and fear of fitness to practice processes were important barriers present across all seven stages of candidacy. The fragmented structure of local services, along with individual factors such as perceived stigma and confidentiality concerns, limited the progression of medical students through the Candidacy Framework (a framework for understanding the different stages of a person's journey to healthcare). Conclusion This study outlines important areas of consideration for mental health service provision and policy development to improve access to and the quality of care for medical students.